Economic evaluation of Suboxone® for substitution treatment of opioid drug dependence in Portugal - Gouveia, Miguel (2015)
Background: According to a recent Portuguese study the prevalence of lifetime consumption of heroin in the global population (age range: 15-74 years) is 0.5%. Methadone is the standard pharmacological treatment, while buprenorphine has been available since 1999 as an alternative treatment. Nevertheless, no comparative economic evaluation of the costeffectiveness of these therapies has been made available. Aim: This study estimates the cost-effectiveness and cost-utility of a fixed dose combination of buprenorphine-naloxone (B/N) versus methadone as substitution treatments for opioid drug dependence from the Portuguese social perspective. Material and Methods: The comparator for B/N was methadone treatment, which is the most common pharmacological therapy and current clinical practice in Portugal. Health gains were measured using the number of heroin-free days per year (indicator of effectiveness) and quality-adjusted life years (QALYs) associated with each treatment. Estimated costs included acquisition, preparation and transport of medication; costs of dispensing and supervision of administration; costs arising from the periodic monitoring of patients and the nonmedical direct costs of crime associated with drug addiction. Results: The B/N combination is associated with an incremental cost-utility ratio of €5,914 per QALY gained. The B/N combination is dominant when the analysis includes costs of crime associated with drug addiction. Conclusions: The results suggest that this combination is cost-effective and has the potential to generate health gains in the target population at a low cost.